USING THE MAPLE SOFTWARE TOOL IN SOLVING A SYSTEM OF LINEAR EQUATIONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article presents an effective way to use information technology in math classes, showing a way to solve linear equations in the MAPLE program. The commands of the actions performed on matrices are given in the MAPLE program, and the method of solving a system of Linear Equations by shifting them to Matrix equations is illuminated by examples.